Respon Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis Sativus L.) Terhadap Pemberian Pupuk Kandang Sapi dan Pupuk Organik Cair Sabut Kelapa - Meci Yuniastuti Rahma; Siska Masrury (Politeknik Negeri Lampung, 2021)
Cucumber production has decreased in 2017, it was still increase, one of production by providing organic matter and good fertilization, therefore it is necessary to respond to growth and production of cucumber plants with fertilization from cow manure and liquid organic coconut coir fertilizer which the NPK nutrient content in both of these organic materials. This study aims to determine the response of growth and yield of cucumber (Cucumis Sativus L.) to cow manure and coconut coir liquid organic fertilizer. This research has been carried out in the village of Sembawa, Banyuasin Regency. The implementation of the study began in March 2021 until May 2021. The design used was a Randomized Block Design arranged in a factorial manner with 9 treatment combinations, each treatment repeated 3 times. The treatmensts were A = Cow Manure, B = Coconut Coir Poc. The parameters observed in this study were plant height (cm), fruit length (cm), fruit diameter (cm), and fruit weight (grams). The results of the analysis of diversity (F test) showed that the interaction between cow manure and coco coir had no significant effect on fruit diameter and fruit weight. The coefficient of diversity (KK) values varied from 3.34% to 11.92%. The resutls of the analysis of the further test of Honest Significant Difference, the best treatment was P2 (cow manure dose 15 tons / 1.8 kg per plot) and S2 (coconut coir poc 15 % concetration). Key words : manure fertilizer, coconut coir liquid fertilizer , cucumber